Serie audiovisual :súper ecuatorianas (historias de vida). - Núñez Zapata, Carlos Andrés (2016)
The audiovisual product is based on a program that represents and tells stories of Ecuadorian women living in the city of Quito. Workers not only at home, but more of the housework devote their efforts to work in the production area related to trade in the city. They are women who engage in unusual activities, which have generally been seen as exclusive male. In view of this it is intended with this product, demonstrate the strength of women to do all kinds of work and to put women as well as real life examples. In this way we want to show the process, to a very advanced stage, claiming women in Ecuadorian society, the same as it visualizes through this audiovisual piece presents. The program is focused on making a tribute to the female gender and present a broad overview of the work of the selected story for this video. The best way to break down concepts and “chauvinist” ideas rooted in society, in the opinion of the authors, is just present an audiovisual product made by men from the male perspective and designed, produced and structured by men